Diseño y elaboración de un protocolo en gerencia de proyectos para el mantenimiento de paradas de planta en la refinerías en Colombia por la empresa Mecánica Asociados S.A.S. (2015)
This document aims to clarify to the reader the low base which different protocols were developed, this first reference to the context in which the protocols are used, specifying the current state of maintenance shutdowns in Colombia, regulations and related documentation and other general aspects. Then the activities for the development of the protocol are set to finally introduce themselves under the respective considerations